Methodological Pluralism in History: Revisiting the New History and Annales Approaches in the Development of Historical Research Themes - Diki Tri Apriansyah Putra (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2025)
Until today, historical studies continue to evolve. The paradigm shift from traditional historical writing has ushered in a new phase for history as a scientific discipline. This study explores the pluralism of historical methodologies by reexamining the New History and Annales approaches in generating new themes within historical scholarship. The central issue addressed in this research concerns the limitations faced by historical studies in developing new and relevant topics. The study aims to provide a conceptual foundation and fresh perspectives on emerging themes in historiography. The findings reveal that methodological pluralism in history enables researchers to more easily identify and explore diverse research themes. History students and scholars are no longer confined to the traditional paradigm that centers solely on grand events and prominent figures. Contemporary historical writing offers a more inclusive, multidisciplinary, and socially relevant perspective, aligning historical inquiry with current societal issues. History is no longer viewed as an ivory tower of knowledge, but as a dynamic field capable of responding to real-world problems.